An intracellular threonine of amyloid-β precursor protein mediates synaptic plasticity deficits and memory loss. - Franco Lombino (Public Library of Science (PLoS), 2013)
Mutations in Amyloid-ß Precursor Protein (APP) and BRI2/ITM2b genes cause Familial Alzheimer and Danish Dementias (FAD/FDD), respectively. APP processing by BACE1, which is inhibited by BRI2, yields sAPPß and ß-CTF. ß-CTF is cleaved by gamma-secretase to produce Aß. A knock-in mouse model of FDD, called FDDKI, shows deficits in memory and synaptic plasticity, which can be attributed to sAPPß/ß-CTF but not Aß. We have investigated further the pathogenic function of ß-CTF focusing on Thr(668) of ß-CTF because phosphorylation of Thr(668) is increased in AD cases. We created a knock-in mouse bearing a Thr(668)Ala mutation (APP(TA) mice) that prevents phosphorylation at this site. This mutation prevents the development of memory and synaptic plasticity deficits in FDDKI mice. These data are consistent with a role for the carboxyl-terminal APP domain in the pathogenesis of dementia and suggest that averting the noxious role of Thr(668) is a viable therapeutic strategy for human dementias.